Searching for promising new perovskite-based photovoltaic absorbers: the importance of electronic dimensionality. Issue 2 (23rd December 2016) - Xiao, Zewen; Meng, Weiwei; Wang, Jianbo; Mitzi, David B.; Yan, Yanfa
Abstract : The concept of electronic dimensionality, i.e., the connectivity of the atomic orbitals that comprise the lower conduction band and upper valence band, is introduced to better account for the device performance of the perovskite-based solar cells. Abstract : Searching for promising nontoxic and air-stable perovskite absorbers for solar cell applications has drawn extensive attention. Here, we show that a promising perovskite absorber should exhibit a high electronic dimensionality. Semiconductors that exhibit a high structural dimensionality, but a low electronic dimensionality have less promise as an absorber, because of barriers to isotropic current flow, enhanced electron/hole effective masses and fundamentally deeper defect states (more effective at causing recombination). Our concept accounts for the device performance of the perovskite-based solar cells reported in literature so far.